The Reflective Reading Corner: Enhancing Literacy and Critical Thinking in Elementary Schools - Triastuti Dian Anggraeni; Banu Setyo Adi; Bambang Saptono; Marwan; Agus Herwanto; Agung Prihatmojo (Universitas Pendidikan Ganesha, 2024)
One of the primary challenges in achieving equitable education quality at the elementary school level is students' low reading literacy skills. This study aims to analyze the effectiveness of reading corners in improving students' literacy and critical thinking skills. The research employed a qualitative design with data collected through interviews, observations, and documentation. The research instruments included tests and documentation. Data collection involved interviews with teachers and students, observations of reading corner activities, and documentation of literacy programs conducted by the school. Data analysis was carried out using thematic analysis to identify patterns and relevant categories. The findings revealed that reading corners effectively enhance students' literacy and critical thinking skills. Students who regularly visited the reading corner were more active in literacy activities, demonstrated higher reading interest, and showed improved critical thinking abilities during learning sessions. Teachers also played a crucial role in managing the reading corner and creating supportive literacy activities. The study concludes that reading corners are an effective tool for improving literacy and critical thinking skills in elementary students. Therefore, schools and teachers are encouraged to continuously develop reading corners to achieve broader positive impacts on student learning outcomes.